Interrelating operational and financial performance measurements in a multiproduct inventory system. (10th October 2011) - Protopappa-Sieke, Margarita; Seifert, Ralf W.
Financial supply chain management and working capital management are increasingly under the spotlight as effective approaches to optimising working capital levels and directing cash flows. Especially in a multiproduct environment, efficient working capital allocation can boost company performance, achieve significant cost savings and demonstrate risk-pooling benefits. In this paper, we focus on the interrelation of working capital and stocking decisions for functional, innovative and heterogeneous product portfolios. We analyse the effect of demand correlation, lead time, payment delays, portfolio sizes, and service level constraints for multiproduct portfolios. Due to the dynamic nature of working capital, we resort to simulation in order to derive managerial insights. Our results attest the importance of payment delays on the profitability of a company. In addition, we demonstrate risk-pooling benefits from a financial perspective.